Identification of Risk Factors for Dupilumab-associated Ocular Surface Disease in Patients with Atopic Dermatitis - Roselie E. Achten; Chantal van Luijk; Lisa van der Rijst; Daphne Bakker; Lotte Spekhorst; Nicolaas Zuithoff; Marie Schuttelaar; Geertruida Romeijn; Angelique Voorberg; Marijke Kamsteeg; Inge Haeck; Marlies de Graaf; et al. (Medical Journals Sweden, 2022)
This study identified risk factors for the development of dupilumab-associated ocular surface disease in patients with moderate-to-severe atopic dermatitis in a large prospective daily practice cohort. Data from the Dutch BioDay Registry were used to assess the risk of developing dupilumab-associated ocular surface disease, by performing univariate and multivariate logistic regression analyses. A total of 469 patients were included, of which 152/469 (32.4%) developed dupilumab-associated ocular surface disease. Multivariate analysis showed a statistically significant association of the development of dupilumab-associated ocular surface disease with a history of any eye disease (history of self-reported episodic acute allergic conjunctivitis excluded) combined with the use of ophthalmic medication at the start of dupilumab (odds ratio 5.16, 95% confidence interval 2.30-11.56, p < 0.001). In conclusion, a history of any eye disease (history of self-reported episodic acute allergic conjunctivitis excluded) combined with the use of ophthalmic medication at baseline was associated with the development of dupilumab-associated ocular surface disease in patients with atopic dermatitis.